HUBUNGAN INFORMASI LAPORAN KEUANGAN NASABAH DENGAN KEPUTUSAN PEMBERIAN PEMBIAYAAN PADA PT. BPRS SAFIR BENGKULU - Fitria Wati; Feri Susanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
Fitria Wati, Feri Susanto; The purpose of this research was to determine the relationship of the customer’s financial statement information with the decision to grant financing in PT.  BPRS Safir Bengkulu. PT. BPRS Safir Bengkulu established to be superior and healthy in Bengkulu Province, provide benefits in economic development, especially people of Bengkulu province, providing professional services and trust in carrying out banking business, and become a business partner community, especially employers. From the results of research conducted showed that the relationship of customer’s financial statement with the decision to grant the provision of financing to PT. BPRS Safir Bengkulu from July 2014 through the month of September 2014 was not all indicators of the information has a significant relationship. Key words: Customer’s Financial Statement Information